2013
DOI: 10.1002/htj.21105
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Viscoelastic Fluid Flowing Through Porous Medium Down Non-uniformly Heated Inclined Plane

Abstract: The stability of a thin layer of viscoelastic fluid flowing through a porous medium down a non-uniformly heated inclined plane with a constant temperature gradient along the plane is considered. The film flow system is influenced by gravity, mean surface tension, thermocapillary forces, viscoelastic forces, porosity, and permeability of porous medium. We seek a solution of the stability problem in a series in small wave numbers, and the obtained results, when the plane is heated in the downstream direction, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…For this paper, we selected typical reservoir rock samples from the study area in the Songliao Basin. We drilled three small samples from the x, y, and z axes in order to determine the parameters of rock mechanics under conditions of changing pore pressure, confining pressure or temperature to analyze the role and influence of Biot's coefficient with respect to microscopic anisotropy (Wu et al, 2014;El-Sayed et al, 2015;Garrido et al, 2015;Grassl et al, 2015;Lu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For this paper, we selected typical reservoir rock samples from the study area in the Songliao Basin. We drilled three small samples from the x, y, and z axes in order to determine the parameters of rock mechanics under conditions of changing pore pressure, confining pressure or temperature to analyze the role and influence of Biot's coefficient with respect to microscopic anisotropy (Wu et al, 2014;El-Sayed et al, 2015;Garrido et al, 2015;Grassl et al, 2015;Lu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the linear instability threshold coincides with the nonlinear stability one. It is worth noting that the stability theory of thermal convection in a fluid‐saturated porous medium has been employed by many authors, for instance, Gaikwad and Dhanraj, 26 El‐Sayed et al, 27 Haddad, 28,29 and Attia et al 30 Other recent work that is employing stability theory in the context of a bidispersive porous medium is due to Franchi 31,32 and Straughan 33,34 …”
Section: Introductionmentioning
confidence: 99%